Lateral Soil Movement Due to Installation of a Single Pile using Jack-in Method - Dewi Hindra Wijaya (Petra Christian University, 2021)
Lateral movement of soil due to the installation of a single pile using jack-in method was studied. The piles considered in this study were 15 piles of the diameter 800 mm. The lateral soil movement was predicted using Plaxis 2D, which incorporated cavity expansion theory as prescribed displacement. The results were compared to the recorded data from the field and those determined using several formulas. The comparison shows that the lateral movement of soil due to the installation of a single pile can be closely estimated using Plaxis 2D that employed a linear prescribed displacement of 0.42r at the pile head and zero at the pile tip. Lateral displacement of soil predicted using Plaxis 2D agrees well with data measured from the field both at the ground surface and along the depth of piles.